Rapid processing window development of Mo-Si-B alloy for electron beam powder bed fusion - Chen, Yong; Böhm, Jonas; Wahlmann, Benjamin; Krüger, Manja; Körner, Carolin (Progress in Additive Manufacturing, 2025)
The multiphase alloy Mo-9Si-8B (at.%) exhibits high oxidation, creep, and fracture resistance at high temperatures. With a melting point of about 2360 °C, it is a promising material for ultra-high temperature applications in turbine engines. However, Mo-9Si-8B (at.%) is difficult to process by traditional manufacturing methods due to its brittleness. Additive manufacturing offers a solution by enabling the production of complex near-net-shape bulk materials (e.g., turbine blades) in a single step. In this study, electron beam powder bed fusion (PBF-EB), which is characterized by extremely high local processing temperatures and associated high powder bed temperatures (i.e., above the brittle-to-ductile transition temperature of the material), was employed to process this Mo-Si-B alloy. The processing window was rapidly developed for the first time using novel strategies that combine high-throughput thermal modeling to predict the melt pool dimensions with in situ electron-optical imaging. High-density bulk Mo-9Si-8B (at.%) samples were successfully fabricated according to the established processing window, and the typical microstructure and phase composition of the as-built samples were analyzed. This novel approach significantly reduces the effort required to generate processing windows, making it highly viable for developing stable processing conditions for new materials in PBF-E
Keywords: Mo-Si-B alloy; Electron beam powder bed fusion (PBF-EB); Process monitoring; Processing window; Thermal modeling